A multistimuli-responsive fluorescent switch in the solution and solid states based on spiro[fluorene-9, 9′-xanthene]-spiropyran. Issue 29 (11th July 2019) - Wang, Lingyun; Xiong, Wei; Tang, Hao; Cao, Derong
Abstract : A solid state stimuli-responsive fluorescent switch based on spiro[fluorene-9, 9′-xanthene]-spiropyran (SFX-2SP ) was reported. Abstract : Multistimuli-responsive fluorescent molecular switches (FMSs), both in solution and solid states, have attracted extensive attention due to their numerous prospects in many functional materials. However, it has long been a serious challenge to develop such materials because of the contrasting aggregation-caused quenching (ACQ) and aggregation-induced emission (AIE) effects. It is especially difficult to achieve FMSs in solid state because the tight molecular packing in aggregated molecules limits the photoswitching phenomenon. In this study, an efficient FMS based on a spiropyran-functionalized spiro[fluorene-9, 9′-xanthene] derivative (SFX-2SP ) was designed and synthesized. TheSFX-2SP not only preserved the isomerization property under visible light/dark and acid/base stimuli in solution but also showed high contrast emission between its ring-closed and ring-open solid states. Moreover, in a polymethyl methacrylate (PMMA) matrix, the cyan/red emission switching upon the stimulation with light and heat was achieved successfully with high reversibility due to the large free volumes caused by the orthogonally interconnected SFX moiety. On regulation with ultraviolet light irradiation, the wettability of theSFX-2SP solid surfaces increased and the contact angles decreased from 85.9° to 75.1°. Therefore, it is promising to generate more solution/solid state photochromic materials through this rational, simple, and facile structural design strategy.